SOSIALISASI MANFAAT INOVASI PENGOLAHAN SINGKONG DESA PETANANG SERTA FUNGSI MEDIA APLIKASI PROMOSI DIGITAL PROGRAM KKN TEMATIK MBKM MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI - Cristina, Natalia Neisya; Hertati, Lesi; Syafitri, Lili; Munandar, Aris; Hendarmin, Rum (Transpublika Publisher, 2022)
Petanang village is a village located in Lembak sub-district, Muara enim district, South Sumatra. In 2022, the population will be around 2,020 people or 689 families, residents per square kilometer. Most of these residents develop cassava into processed chips with the basic ingredients of cassava, which are named Kelasan. Class is a type of snack such as chips that comes from Petanang village, Lembak sub-district, Muara Enim Regency. From this process, a home-based MSME is created which is carried out by the residents of the Petanang village. Sales of first-class products are carried out within the village and also outside the village of Petanang. To further increase the potential that exists in Petanang village, Indo Global Mandiri University students try to help develop innovations for Cassava Processing in Petanang Village and Media Functions for Digital Promotion Applications for the MBKM Thematic Community Service Program, Indo Global Mandiri University students make new product innovations, namely Roasted Beef Flavored Cassava Chips. In addition to helping MSME actors create new products that can be marketed in digital media to increase the income of rural communities. Students also provide direction on financial reports and how to market a product in order to dominate the market.